A Matter of Principle. - Chambers, R. J. (The Accounting Review, 1966)
Certain developments inspired the Accounting Principles Board to approve the preparation of the "Inventory of Generally Accepted Accounting principles for Business Enterprises," ARS No. 7. It was long wished for an inventory of generally accepted accounting principles; for whether one wishes to adopt, to rebut, or even simply to think about these principles, it would be useful to know what they are. But the inventory is not a simple listing. A great deal of ARS No. 7 is devoted to the justification of the listed propositions and to the rebuttal of objections to them. The study presented in the article is argumentative and as such invites cross-arguments. The study is unquestionably valuable. It makes very clear the massive difficulties with which the users of financial statements have to contend. The inventory, at least by implication, makes it abundantly clear that great changes are necessary to put contemporary practices on the footing of the requirements of the statutory principle, and even greater changes to establish practice on the ethical footing which have been suggested and is ideally more solid and dependable than a statutory specification.